Aesthetics of Delirium in Contemporary Latin American Narrative - Acevedo Carvajal, Juan Manuel; Álvarez Orozco, Andrea Estefanía; Millán Velásquez, Yenni Zulena (Disertaciones, 2020)
The fundamental objective of this article is the configuration of a constellation of delusional fictions in contemporary Latin American literature, based on the conceptualization of literary delusion and the analysis of the construction process of the delusional narrative. Given that some Latin American narrators display delusional fictions in our days, and there is a large number of cases, where delirium is evident in the literature of our continent, authors such as: Mario Bellatin, Roberto Bolaño, Rita Indiana Hernández, Horacio Castellanos Moya, Cristina Rivera Garza, among others. Consequently, attention will be focused on creating a critical basis for the interpretation of the delusion of some characters in contemporary Latin American literature, as a cultural construct that transgresses the social order, and is assumed as resistance and articulation of creative praxis.